Advertising with Supply Control: Some Implications of Norwegian Whitefish Export Promotion. (December 2020) - Williams, Gary W.; Capps, Oral
Abstract : An issue for generic advertising in agricultural markets with unregulated supplies is that the promotion-induced demand shift could lead to a supply response that substantially attenuates the price effects of the promotion. For the generic promotion of fish exports, however, the concern is generally just the opposite—the possibility that extensive government supply controls could render promotion efforts to expand export sales ineffectual due to little or no supply response. This study considers the effects of government whitefish (cod, haddock, and others) supply controls on the effectiveness of the Norwegian Seafood Council (NSC) whitefish export promotion program. We use an econometric simulation model to measure the effectiveness and returns to NSC whitefish export promotion under a range of possible export supply control conditions. Results indicate that effective supply control maximizes the return to promotion and that ineffectual supply control imposes a potentially large opportunity cost on the promoting industry.